Determination of the degree of sulfonation in cross-linked and non-cross-linked Poly(ether ether ketone) using different analytical techniques - Abdul G. Al Lafi; Mohammed S. Rihawy; Abdul W. Allaf; Ali Alzier; Reem Hasan (Heliyon)
The degree of sulfonation (DS) is a key property of sulfonated polymers, as it significantly influences their swelling behaviour, conductivity and mechanical properties. Accurately determining the DS is essential for optimizing these materials for various applications. In this work, the DS of sulfonated poly (ether ether ketone) (SPEEK) was evaluated using a combination of analytical techniques, including titration, back titration, Fourier Transform Infrared (FTIR), Ultra-Violet (UV) and proton nuclear magnetic resonance (1H NMR) spectroscopies, Thermogravimetric analysis (TGA), Rutherford backscattering (RBS) and particle induced X-ray emission (PIXE) analysis. Both non-cross-linked and cross-linked SPEEK were examined to assess the advantages and limitations of these methods. Classical approaches, such as titration and back titration are suitable for all sulfonated samples; however, they are limited by challenges like the extended time required for neutralization reaction due to hydrogen bonding between sulfonic acid groups. In contrast, molecular spectroscopic methods particularly UV and 1H NMR spectroscopy, are more efficient for soluble samples. 1H NMR spectroscopy is especially accurate, though it necessities additional steps, such as determining T1 relaxation times to ensure complete magnetization recovery. FTIR spectroscopy emerges as a versatile and effective method for DS determination across all samples types, particularly when enhanced with ATR accessories and calibrated with 1H NMR data. Combining with two-dimensional correlation spectroscopic analysis further improves its reliability.